Efficient separation of arsenic species of oxyanion As (III) and As (V) by using effective polymer inclusion membranes (PIM). (March 2023) - Govindappa, Harshith; Abdi, Gholamreza; Uthappa, U.T.; Sriram, Ganesan; Han, Sung Soo; Kurkuri, Mahaveer
Abstract: The heavy metal contaminant arsenic exist in the form of arsenite (As(III)) and arsenate (As(V)) ions. These ions are highly carcinogenic that are usually present in the ground water. To date, most of the designed polymer inclusion membrane (PIM) involved only about separation without differentiating the oxidation states. Thus, there is a research gap on separation of element with different oxidation states. Thus, this study addresses such research gap which have been not explored previously. To extract such ions from water, the present study involves fabrication of PIM by varying the compositions of the base polymer, carrier and plasticizer. Also effect of the strip solution, and transport properties were studied. High performance membrane was obtained with 50% (w/w) Aliquat 336 and 50% (w/w) Cellulose triacetate (CTA). The production of 1 m 2 of PIM may cost approximately 0.08–0.16$. Also, we have combined the separation capacity of polymer inclusion membrane (PIM) with the sensitivity and elemental detection using atomic absorption spectrometry (AAS) to detect and separate As(III) and As(V). AAS is limited to detecting only elemental arsenic (As) and does not distinguish between As(III) and As(V). Further, to address such limitations in this current study we were able to separate As(V) from As(III) within 5 h. In addition, to provide sole solution a device was fabricated to extract As(V) in the field studies which displayed outstanding efficiency of 99.7 ± 0.2%. The extracted samples was tested in AAS to differentiate between oxidation states of the arsenic species and these important results are supportive in finding out the redox potential of water and for other geochemical explorations. Graphical abstract: Set up for extraction of Arsenic. Image 1 Highlights: Polymer Inclusion Membrane (PIM) developed for separation of Arsenic(V) and Arsenic (III) in water. Production cost of 1 m 2 of PIM is approximately 0.002–0.004 $. Device is fabricated for the separation of Arsenic(V) from Arsenic (III) in field studies. Using device the oxidation states of arsenic can be differentiated using Atomic absorption spectroscopy (AAS).